37.8k views
0 votes
Which expression is equivalent to 3x^-6y^-3/15x^2y^10

User Silly
by
5.5k points

2 Answers

2 votes

(3x^(-6)y^(-3))/(15x^2y^(10))=(1)/(5)x^(-6-2)y^(-3-10)=(1)/(5)x^(-8)y^(-13)=(x^(-8)y^(-13))/(5)=(1)/(5x^8y^(13))\\\\Used:\\\\(a^n)/(a^m)=a^(n-m)\\\\a^(-n)=(1)/(a^n)
User Karbert
by
5.7k points
3 votes

Answer:


(1)/(5x^(8)y^(13))

Explanation:


(3x^(-6)y^(-3))/(15x^2y^(10))

To find out equivalent expression we need to simplify it


(3)/(15) =(1)/(5) divided 3 on both sides

To simplify variables , use exponential property


(a^m)/(a^n) =a^(m-n)


(x^(-6))/(x^2) =x^(-6-2)=x^(-8)


(y^(-3))/(y^(10)) =y^(-3-10)=x^(-13)

Our expression becomes


(x^(-8)y^(-13))/(5)

To remove negative exponent we move the variable with exponent to the denominator


(1)/(5x^(8)y^(13))

User Ququzone
by
6.5k points